Peningkatan derajat kesehatan masyarakat Bagan Sinembah melalui pengelolaan sampah rumah tangga menjadi barang bernilai ekonomi - Huriatul Masdar; Fifia Chandra; Arfianti Arfianti; Yulia Irvani Dewi (Unri Conference Series: Community Engagement, 2019)
Household waste if not managed properly can cause various health problems. Good management of household waste can have economic value and improve the economy of community. Organic waste can be processed into compost that is useful for agricultural land while non-organic waste can be recycled into high-value items. This waste management problem also occurred in Bagan Sinembah Subdistrict, Rokan Hilir Regency. Through community service activities at University of Riau, socialization of organic and non-organic waste management, composting training and decoupage art applications on used goods in households were conducted. The level of success of this activity is considered good in quality, but the quantity of trainees is still lacking. Increasing the number of target communities needs to be done so that the waste management efforts at Bagan Sinembah become more optimal.